Kajian kefalometrik (Studi perbandingan antara suku Jawa dan suku Naulu di pulau Seram, Maluku Tengah - Neni Trilusiana Rahmawati; M Hirai; E Suryadi; Mansyur Romi; T Jacob (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2003)
Background: Regional variation in anthropometric measurements and anthroposcopic always found, even in one population or subrace. Therefore, it is interesting to study these composite physical traits in rural population of Indonesia with different environment. Objectives: To examine the characteristics of the cephalometry of Javanese population in Yogyakarta, and to compare with Naulunese population in Seram Island of Middle Maluku. Methods: 100 people of Java in Yogyakarta consists of 50 males and 50 females, aged 20 - 75 years, were studied and compared with Naulu people (62 males and 110 females). Stature, weight, maximum head breadth and length, minimal frontal breadth, bizygomatic breadth, face height, breadth and height of nasal were measured. Analysis of variance and t-test were used to study the difference of cephalometric between males and females of Javanese population, and to study the difference between Javanese and Naulunese populations. Results: The results showed that Javanese population has mesocephalic head, wide forehead, narrow face and mesorhine nasal type. There were significant differences between Javanese males and females in regard to their height, weight, bizygomatic breadth, face height, nasal breadth and nasal index. There were significant differences between Javanese and Naulunese populations in terms of their height, head breadth, minimal frontal breadth, face height, frontoparietalis and facial index. In addition, there were similarities of head shape, width forehead and nasal shape among both populations. Conclusions: The finding indicated that Javanese and Naulunese populations have mesocephalic head, wide forehead and mesorhine nasal type.Key words: cephalometric - Javanese - Naulunese - cephalic index - anthropometric